THE RELATIONSHIP OF GENDER INEQUALITY FROM CAROLE PATEMAN'S PERSPECTIVE IN ANTON KURNIA'S NOVEL MAJNUN AND ITS USE AS LITERARY TEACHING MATERIAL IN HIGHER EDUCATION - Panji, Panji Kuncoro Hadi; Kasimbara, Devi Cintia; Putri, Meilani Alvindha (UNIVERSITAS PGRI YOGYAKARTA, 2024)
This research aims to describe and explain unequal relations between women and men from Carole Pateman's perspective in the novel Majnun by Anton Kurnia, and its use as literary teaching material in universities. Based on the object, this research is a qualitative descriptive research. Data was collected through library methods. Data were analyzed using the content analysis method using Carole Pateman's reading method. The research results show that in the novel Majnun by Anton Kurnia there are unequal relations between women and men in terms of marital status. This is because in essence marriage is only a sexual contract.